A simple colorimeter based on microcontrollers to detect food dyes. (April 2020) - Yulkifli,; Wulandari, D A; Ramli, R; Etika, S B; Imawan, C
Abstract: A simple colorimeter has been successfully designed using a microcontroller to detect food dyes. This article describes the performance specifications and design specifications of the colorimeter that was designed as a detector for food dyes using a photodiode sensor and a light emitting diode lamp as a source. System performance specifications consist of mechanical systems that are supported by electronic systems. Data collection techniques were carried out directly and indirectly. Color absorption data were measured directly using an ultraviolet-visible spectrophotometer and indirect absorption data is determined by the voltage that was processed by the microcontroller. The test was carried out by measuring 10 variations in the concentration of food dye liquid, in the range of 0.1% - 1.0%. Measurements were made with 10 repetitions. The data were analyzed in two ways, statistically and graphically. The accuracy of the colorimeter design was done by comparing it with the measurement results from the ultraviolet-visible spectrophotometer. The average percentage of errors are 1.7% and the average relative accuracy of the system is 93.3%. These results indicate that a simple colorimeter can be used to measure the concentration of food dyes quickly and with good accuracy.